IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI BUDAYA SEKOLAH DI SD N KOTAGEDE 3 YOGYAKARTA TAHUN AJARAN 2016/2017 - Melani Septi Arista Anggraini; Heri Maria Zulfiati (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to describe the implementation of character education through school culture in SD N Kotagede 3, Umbulharjo Yogyakarta. This research is a descriptive study using a qualitative approach. Subjects of this study consisted of one principal, six teachers, two teachers extracurricular, three students of class IV, V and VI, and the school committee. Selection of research subjects have been with a certain consideration. The experiment was conducted in SD N Kotagede 3, Umbulharjo Yogyakarta. The technique of collecting data using interviews, documentation and observation moderate because the researchers only do some of the activities undertaken by the speaker. Data analysis techniques used during this study using an interactive model Miles and Huberman, namely data collection, data reduction, data presentation, and conclusion. The results showed that the implementation of character education through a school culture that is carried out in SD N Kotagede 3 includes intrakurikuler including 5S, MCC, breakfast, tadarus classical, gymnastics mass, flag ceremony, Thursday pahingan, warning big day, smutlis, waste sorting and go library. In addition intrakurikuler activities, the implementation of character education through school culture in SD N Kotagede 3, Umbulharjo, Yogyakarta is also manifested in extracurricular activities, namely the scouts, TPA, ICT, dance, batik, marching band, gamelan, music, alteltik, karate and qiroah. Character values that are formed in the implementation of character education through school culture held in SD N Kotagede 3 covers religious, disciplined, responsible, independent, creative, environmental care, social care, honest, hard work, patriotism, and love to read. Inhibiting factors and support in implementing character education through school culture in SD N Kotagede 3, namely, teachers, students, parents and facilities can be a contributing factor as well as inhibiting the culture of the school, depending on how the responses and action given every component on any activities carried out.